Common Options and Overlooked Alternative for Drainage of Inaccessible Presacral Abscess: A Case Report - Kodzis, Evelina; Jocius, Donatas; Lapteva, Ona; Kručaitė , Rugilė (Acta medica Lituanica, 2021)
Purpose. To demonstrate options and alternative for drainage of inaccessible presacral abscess by the example of a rare clinical case of pyogenic spondylodiscitis, transsacraly drained under a combination of two interventional techniques – CT-guided bone biopsy and abscess drainage.Materials and methods. A 55-year-old patient with history of recurrent paravertebral abscesses previously treated with antibiotic therapy was referred to our institution experiencing lower back pain and weakness in both lower extremities. Computed tomography revealed pyogenic spondylodiscitis along with left facet joint destruction and presacral abscess located in ventral sacral surface. Due to inaccessible abscess location, it was decided to perform CT-guided percutaneous transsacral abscess drainage. An 8G bone marrow biopsy needle was used to penetrate the sacrum and create a path for drainage catheter placement. Using the Seldinger technique 8 Fr drainage catheter was inserted into abscess cavity.Results. Neither early nor late procedure-related complications occurred. Sixteen days after drainage procedure, the catheter was withdrawn as patient’s condition improved and the outflow of pus had reduced considerably.Conclusions. Despite being rarely used, CT fluoroscopy-guided transsacral drainage approach is considered to be minimally invasive and in some cases the only viable option for drainage of pyogenic spondilodiscitis of the lumbosacral junction.
Keywords: Case report; presacral abscess; pyogenic spondylodiscitis; transosseus drainage; transsacral approach